Identification of imidazo[4,5-c]pyridin-2-one derivatives as novel Src family kinase inhibitors against glioblastoma - Lishun Zhang; Zichao Yang; Huiting Sang; Ying Jiang; Mingfeng Zhou; Chuan Huang; Chunhui Huang; Xiaoyun Wu; Tingting Zhang; Xingmei Zhang; Shanhe Wan; Jiajie Zhang (Taylor & Francis Group, 2021)
Glioblastoma multiforme (GBM) is the most common and malignant primary brain tumour in the central nervous system (CNS). As the ideal targets for GBM treatment, Src family kinases (SFKs) have attracted much attention. Herein, a new series of imidazo[4,5-c]pyridin-2-one derivatives were designed and synthesised as SFK inhibitors. Compounds 1d, 1e, 1q, 1s exhibited potential Src and Fyn kinase inhibition in the submicromolar range, of which were next tested for their antiproliferative potency on four GBM cell lines. Compound 1s showed effective activity against U87, U251, T98G, and U87-EGFRvIII GBM cell lines, comparable to that of lead compound PP2. Molecular dynamics (MDs) simulation revealed the possible binding patterns of the most active compound 1s in ATP binding site of SFKs. ADME prediction suggested that 1s accord with the criteria of CNS drugs. These results led us to identify a novel SFK inhibitor as candidate for GBM treatment.